Pengaruh Struktur Modal Terhadap Nilai Perusahaan Dengan Pertumbuhan Perusahaan Sebagai Variabel Moderating (Studi Pada Perusahaan Manufaktur Sektor Makanan dan Minuman) - Sugiarto, Ricky Radius; Edward, Fenty Dwijayanti; Nugroho, Nugroho (STKIP Singkawang, 2025)
This study aims to test and find empirical evidence regarding: (1) there is a positive influence of capital structure on company value, (2) there is a positive influence of company growth on company value, and (3) there is a positive influence of capital structure on company value with company growth as a moderating variable. The sample used in this study was a manufacturing company listed on the Indonesia Stock Exchange during a 4-year observation period (2010-2013). The total sample was 13 companies. Data were collected using a purposive sampling method. The results based on moderated regression analysis (MRA) showed that: (1) capital structure did not affect company value, (2) company growth affected company value, and (3) capital structure affected company value with company growth as a moderating variable. Thus, the research hypothesis was not empirically supported.